Cloud-Based Smart Attendance For Engagement Analytics - Aziman, Abdullah; Wan Nor Afiqah, Wan Othman; Adzhar, Kamaludin; Asar, Abdul Karim (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
Cloud-based smart attendance is a novel tool that integrates comprehensive student engagement in the attendance taking process. It is very simple and practical to be adopted by educators for blended learning strategy. It is designed to promote cognitive, emotional and behavioral engagement of the student in the class. With analyticsready capability in this application, it is very practical for implementing engagement analytics. Since the application is hosted on the cloud platform, it is very potential for global-scale adoption to improve the quality of education in meeting the sustainable development goals (SDG) 4.